Data analysis of the phd work: "Experimental realization of U(1) gauge invariance in ultracold atomic mixtures" - Mil, Alexander (Universität, 2020)
Phd Thesis Abstract: "This thesis reports on the experimental realization of an elementary building block for analog quantum simulation of a U(1) l...
Gesehen am 05.01.2021
Keywords: Forschungsdaten; Datenbank